Experimental Study on Amine-Functionalized Carbon Nanotubes’ Effect on the Thermomechanical Properties of CNT/Epoxy Nano-composites - Seyyed Mahdi Hosseini Farrash; Jalil Rezaeepazhand; Mahmoud Shariati (Mechanics of Advanced Composite Structures)
This paper investigated the effect of the amine-functionalized carbon nanotubes (CNTs) on the thermomechanical properties of CNT/epoxy nanocomposites. Mechanical stirring and ultra-sonication were utilized to uniformly disperse CNTs into the epoxy matrix. Non-functionalized and amine-functionalized CNTs with different weight percentages (wt. %) were mixed into the epoxy resin. Using standard tensile and dilatometry test specimens, this paper determined Young’s modulus, ultimate strength, strain at break, coefficients of thermal expansion, glass transition temperature (Tg), and thermal strain at Tg of the specimens. Neat epoxy, non-functionalized CNT/epoxy (0.25 and 0.5 wt. % CNTs), and functionalized CNT/epoxy (0.25 and 0.5 wt. % functionalized CNTs) nanocomposites were studied. The results indicated that adding 0.25 wt. % functionalized CNTs into the epoxy resin had the greatest effect on Young’s modulus and the nanocomposites’ coefficient of thermal expansion. Moreover, adding CNTs into the epoxy resin decreased the ultimate strength, strain at break, and coefficient of thermal expansion of the specimens.